NEW TECHNIQUES IN DROUGHT ANALYSIS - Subrahmanyam, V P; Sastri, C V S (Annals of Arid Zone, 2016)
One of the still intriguing aspects of drought is its prediction This is mainly on account of the non- existence of reliable periodicities in the occurrence of droughts. But it has been learnt for. certain that droughts, unlike floods, do not descend all of a sudden without warning, but they require extended periods of time to develop. Accordingly, it has been reported that droughts have an origin, spread as well as decay. Hence synoptic and dynamic approaches to this problem are believed to yield objective results and render drought prediction possible. Thus in order to study the spread aspect of drought in the Central Deccan region in South India, aridity anomalies on an annual basis are obtained and regional patterns are prepared. Maps that depict the changing patterns of aridity for the sequential drought situation 1897-1901 are prepared and presented. With a view to obtain a closer picture of the movement of arid patterns or the so called spread of drought, the monsoon season (June-September) in the drought year 1941 has been analysed and spread diagrams are prepared. Departures of monthly wa’er deficiencies from climatic values at 18 Meteorological Stations in the region have been made use of in preparing the maps. These diagrams clearly indicate not only the zones of intense drought condition but also any changes in their intensity and location from month to month. An important aspect in agricultural and hydrological planning is the ’duration’ of a drought in relation to its intensity. The duration of a drought spell is as important a study as its intensity itself in as much as both of them together determine the ultimate effect of water shortage on the economic situation. Mild droughts of prolonged duration are said to have more crippling effects than severe ones of brief duration. Hence the duration aspect of drought demands serious attention and requires special techniques of study. Following the cumulative deviation techniques and making use of the monthly water deficiency values obtainable from the water budgeting procedure of Thornthwaite, attempts are made in Ihis paper to obtain severity indices for drought spells of different duration. Cumulative deviation diagrams thus prepared for two stations in Andhra Pradesh are presented and discussed. This technique when applied after the study of duration and severity of a number of stations from the different climatic zones of South India enables an objective categorization of droughts, severity indices obtained’ from the above method serving as criteria.